Energy-Saving Synthesis of Functional CoS2/rGO Interlayer With Enhanced Conversion Kinetics for High-Performance Lithium-Sulfur Batteries - Feng, Junan; Li, Yahui; Yuan, Jinshi; Zhao, Yuling; Zhang, Jianmin; Wang, Fengyun; Tang, Jie; Song, Jianjun (Frontiers in Chemistry, 2022)
Lithium sulfur (Li-S) battery has exhibited great application potential in next-generation high-density secondary battery systems due to their excellent energy density and high specific capacity. However, the practical industrialization of Li-S battery is still affected by the low conductivity of sulfur and its discharge product (Li2S2/Li2S), the shuttle effect of lithium polysulfide (Li2Sn, 4 ≤ n ≤ 8) during charging/discharging process and so on. Here, cobalt disulfide/reduced graphene oxide (CoS2/rGO) composites were easily and efficiently prepared through an energy-saving microwave-assisted hydrothermal method and employed as functional interlayer on commercial polypropylene separator to enhance the electrochemical performance of Li-S battery. As a physical barrier and second current collector, the porous conductive rGO can relieve the shuttle effect of polysulfides and ensure fast electron/ion transfer. Polar CoS2 nanoparticles uniformly distributed on rGO provide strong chemical adsorption to capture polysulfides. Benefitting from the synergy of physical and chemical constraints on polysulfides, the Li-S battery with CoS2/rGO functional separator exhibits enhanced conversion kinetics and excellent electrochemical performance with a high cycling initial capacity of 1122.3 mAh g-1 at 0.2 C, good rate capabilities with 583.9 mAh g-1 at 2 C, and long-term cycle stability (decay rate of 0.08% per cycle at 0.5 C). This work provides an efficient and energy/time-saving microwave hydrothermal method for the synthesis of functional materials in stable Li-S battery.